Participatory forest management in conservation areas: the case of Cwebe, South Africa - Grundy, I.M.; Campbell, Bruce M.; White, R.M.; Prabhu, Ravi; Jensen, S.; Ngamile, T.N. (2004)
South Africa, influenced by global trends towards good governance and sustainable natural resource management, has begun to adopt a participatory management approach to state-owned indigenous forests. This study, in a remote communal area and State Forest in the Eastern Cape, sought to understand the importance of forest products to local users, together with the relationships between key stakeholders and institutions involved in use and management of State Forest resources. The importance of the Reserve in local peoples' livelihood strategies was clearly revealed but, in the absence of a functional, locally legitimate management body, the Reserve is being over exploited, with local villagers and outsiders capitalizing on low forest rents and lack of enforcement of rules. A de facto open access system is therefore in place. Intensive institution-building is necessary for any participatory management system to be successful, including provisions to: transfer power to the community management body clearly and without ambiguity - if necessary, providing a role within it for the traditional leadership; provide the community management body with adequate financial and other resources; assist the community management body to draw up management plans; propagate and enforce regulations; and support the management body to enable it to provide effective, acceptable monitoring of forest use and regulation.